2014
DOI: 10.1007/s12012-014-9297-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Safety of TGF-β Receptor I Kinase Inhibitor LY2157299 Monohydrate in Cancer Patients in a First-in-Human Dose Study

Abstract: Transforming growth factor-beta (TGF-β) signaling plays an important role in the fetal development of cardiovascular organs and in the repair mechanisms of the heart. Hence, inhibitors of the TGF-β signaling pathway require a careful identification of a safe therapeutic window and a comprehensive monitoring of the cardiovascular system. Seventy-nine cancer patients (67 glioma and 12 solid tumor) enrolled in a first-in-human dose study and received the TGF-β inhibitor LY2157299 monohydrate (LY2157299) as monoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…8 It is known that TGF-β plays a pivotal role in repair mechanisms of the heart and in pre-clinical development, small-molecule ALK5 inhibitors like SD-208 were found to be cardiotoxic on prolonged application in rats, 22 while in clinical trials in humans cardiac toxicity was found to be acceptable. 23 A preferred strategy for combining TGF-β-receptor kinase inhibition with ROR1-CAR T-cell therapy may therefore be to use SD-208 shortly after CAR T-cell infusion to create a time window of protection from TGF-β. Ideally, a single (or short term) treatment with SD-208 may render CAR T-cells resistant to TGF-β for a sufficient amount of time to augment the antitumor effect.…”
Section: Open Accessmentioning
confidence: 99%
“…8 It is known that TGF-β plays a pivotal role in repair mechanisms of the heart and in pre-clinical development, small-molecule ALK5 inhibitors like SD-208 were found to be cardiotoxic on prolonged application in rats, 22 while in clinical trials in humans cardiac toxicity was found to be acceptable. 23 A preferred strategy for combining TGF-β-receptor kinase inhibition with ROR1-CAR T-cell therapy may therefore be to use SD-208 shortly after CAR T-cell infusion to create a time window of protection from TGF-β. Ideally, a single (or short term) treatment with SD-208 may render CAR T-cells resistant to TGF-β for a sufficient amount of time to augment the antitumor effect.…”
Section: Open Accessmentioning
confidence: 99%
“…In a recent clinical doseescalation analysis, the TbRI kinase inhibitor LY2157299 monohydrate (also named galunisertib) proved to be efficacious against malignant glioma (Rodon et al 2015a,b). Previous animal experiments reported severe cardiac side effects of TbRI kinase inhibitors; however, no cardiotoxicity was recorded in patients treated with galunisertib, providing support for the possibility that anti-TGF-b drugs can be clinically useful (Kovacs et al 2015).…”
Section: Tgf-b Family Receptorsmentioning
confidence: 78%
“…During hold of the clinical trial, considerable effort was invested in developing biomarkers of drug response and undertaking PK/PD modeling to define a better therapeutic window for drug response (Gueorguieva et al 2014). Phase I and II studies for galunisertib subsequently incorporated careful monitoring of possible adverse cardiac events using circulating biomarkers, such as troponin I, brain natriuretic protein (BNP) and highsensitivity C-reactive protein (hs-CRP), echocardiography Doppler imaging for possible mitral and tricuspid valve regurgitation, and screening for potential aneurysms of the ascending aorta and aortic arch by computer tomography (CT) or magnetic resonance imaging (MRI) Kovacs et al 2015;Rodó n et al 2015b;Brandes et al 2016). In a clinical safety study (Kovacs et al 2015), only one of 79 patients treated showed an increase in cardiopathologic grade, and then only from a baseline of normal to a mild pathology, as assessed by Doppler.…”
Section: Monitoring and Prevention Of Tgf-b Blockade-induced Drug Toxmentioning
confidence: 99%
“…In the field of SMIs, some of the first clinical trials for TbRI inhibitors have recently been published Kovacs et al 2015;Rodó n et al 2015a,b;Sepulveda-Sánchez et al 2015;Brandes et al 2016), with more in the pipeline. So far, all published clinical studies used the TbRI SMI drug, galunisertib, whereas an additional 12 interventional trials are ongoing with this drug, and another trial uses the TbRI SMI TEW-7197 (Table 2) (Jin et al 2014;Son et al 2014;Naka et al 2016).…”
Section: Small Molecule Kinase Inhibitorsmentioning
confidence: 99%